Key factors influencing economic relationships and communication in European food chains (FOODCOMM) : review of sausage and rye bread chains in Finland - Suvanto, Hannele (Raportteja / Helsingin yliopisto, Ruralia-instituutti, ISSN 1796-0630, 2007)
Tiivistelmä.
Keywords: yhteistyö; tuotanto; sopimustuotanto; sianliha; ruisleipä; ruis; markkinat (taloustiede); makkarat; maatalousyrittäjät; liikesuhteet; lihateollisuus; lihantuotanto; leipomoteollisuus; elintarviketuotanto; elintarviketeollisuus; elintarvikeala